“You Feel Like You Did Something So Wrong”: Women's Experiences of a Loved One's Child Sexual Abuse Material Offending - Salter, Michael (Violence against women, 2024)
This article examines the experiences of female partners and relatives of child sexual abuse material offenders and the (il)legibility of their experiences within prevailing theoretical frameworks and policy responses to violence against women. Drawing on survey and interview data with clients of a specialist support agency, we situate the lack of understanding and support available to these women within the systematic depoliticization of child sexual abuse. The article traces how women developed their own social critique of child sexual exploitation as a form of gendered violence and called for a feminist reengagement with the politics of child sexual abuse.